LESSONS LEARNED ON THE EFFECTIVENESS OF THE MICROECONOMIC PROMOTION AND DEVELOPMENT STRATEGY UNDER THAI NIYOM YUNGYUEN PROJECT (200,000 BAHT PER VILLAGE OR COMMUNITY) TO IMPROVE THE QUALITY OF LIFE FOR GRASSROOTS SECTOR - Wisutthirattanakun, Siriwan (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
The purposes of this research article were to 1) learn lessons on the effectiveness of the microeconomic promotion and development strategy to improve the quality of life for the grassroots sector of Khlong 15 community (Watprasitthivate), Bangplakot sub-district, Ongkharak district, Nakhon-Nayok province 2) study factors affecting the effectiveness of the project, and 3) build a development model effectiveness project. Qualitative research was conducted by in-depth interviews with 44 key informants through purposive sampling. The qualitative data obtained from data collection were analyzed by inductive interpretation. The results showed that: 1) effectiveness of the project: (1) context evaluation indicated that project objectives determination is consistent with problems and needs of people in the community, (2) input evaluation, there are appropriate and sufficient inputs, (3) process evaluation, there is a clear operating procedure and in accordance with the established plan, community participation emphasis, (4) product evaluation can solve the problem and respond to the needs of people in the community as well. 2) the factors affecting the effectiveness of the project are participation, leadership, resources, cognition, and motivation, respectively. 3) a development model effectiveness of the project comprises 3 parts namely; (1) the process (2) factors most affecting effectiveness and (3) the effectiveness of the project.